2005
DOI: 10.1177/1721727x0500300203
|View full text |Cite
|
Sign up to set email alerts
|

Distal Mucosal Site Stimulation by Kefir and Duration of the Immune Response

Abstract: Kefir is a fermented milk (drink) produced by the action of lactic acid bacteria, yeasts and acetic acid bacteria. We recently reported a comparative study on the effect of kefir containing viable or non-viable bacteria by studying their modulatory activity on the intestinal immune response. A functional dose was established in a murine model and the pattern of regulatory and pro-inflammatory cytokines induced was also studied. The existence of a common mucosal immune system implies that the immune cells stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
1
14
0
4
Order By: Relevance
“…Several studies confirm the beneficial effects of kefir, such as the capacity to modulate the intestinal mucosal immune response in mice, enhance the phagocytic activity of peritoneal and pulmonary macrophage, furthermore, the capacity to enhance the mucosal immune system in distal sites (bronchial tissue) (Vinderola et al, 2005a;Vinderola et al, 2005b). On studies performed by Vinderola et al (2005aVinderola et al ( , b, 2006, the authors observed that different components of kefir present an in vivo role role as oral biotherapeutic substances capable of stimulating immune cells of the innate immune system or to promote cell-mediated immune responses against tumours and also against intracellular pathogenic infections.…”
Section: Evaluation Of Probiotic Potential In Isolated Yeastsmentioning
confidence: 96%
“…Several studies confirm the beneficial effects of kefir, such as the capacity to modulate the intestinal mucosal immune response in mice, enhance the phagocytic activity of peritoneal and pulmonary macrophage, furthermore, the capacity to enhance the mucosal immune system in distal sites (bronchial tissue) (Vinderola et al, 2005a;Vinderola et al, 2005b). On studies performed by Vinderola et al (2005aVinderola et al ( , b, 2006, the authors observed that different components of kefir present an in vivo role role as oral biotherapeutic substances capable of stimulating immune cells of the innate immune system or to promote cell-mediated immune responses against tumours and also against intracellular pathogenic infections.…”
Section: Evaluation Of Probiotic Potential In Isolated Yeastsmentioning
confidence: 96%
“…It has been reported that EPS derived from these LAB may enhance immunological functions such as proliferation of T-lymphocytes, macrophage activation and induction of cytokines (interferon-g, interleukin-1,a) and may have the capacity to modify some macrophage and splenocyte functions (Kitazawa et al, 2000;Sato et al, 2004;Vinderola, Perdigó n, Duarte, Farnworth, & Matar, 2006). The water-soluble EPS (kefiran) from kefir grains was demonstrated to have immunomodulating capacity in a murine model; this has the capacity to increase the phagocytic activity of peritoneal and pulmonary macrophages and to modulate the mucosal response at distant sites (Vinderola et al, 2005a) and also effect the cytokine production by cells of the innate immunity-adherent populations of Peyer's patches and peritoneal macrophages (Vinderola, Perdigó n, Duarte, Farnworth, & Matar, 2005b). It has also shown to have the property of retarding tumour growth when administrated orally, probably through T-cell and not through B-cell participation (Zubillaga et al, 2001).…”
Section: Polysaccharide Biosynthesismentioning
confidence: 97%
“…There are several studies investigating its immunomodulatory (Vinderola et al, 2005a), anti-inflammatory (Rodrigues et al, 2005), and anti-neoplastic and pro-digestive effects (Saloff-Coaste, 1996). It was also demonstrated that while kefir induced a typical Th2 response by increasing the number of IL-4+, IL-6+, and IL-10+ cells, pasteurized kefir induced simultaneously the production of INF-g and TNF-a (Vinderola et al, 2005b).…”
Section: Introductionmentioning
confidence: 96%